Information Hiding Techniques Using Network Protocols - Manar Kashmola; Ameera Sallo (Al-Rafidain Journal of Computer Sciences and Mathematics)
The covert channels of type covert storage channels were used in this research to hide textual data or an (image hiding secrete data) in the transmission protocol layer and the internet protocol layer of TCP/IP module. We use IP protocol in designing covert channel by using Identification field, and use TCP protocol in designing covert channel by using Urgent Pointer  field, and UDP by using Source Port field. Finally ICMP protocol by using Echo request message and Message field. The result of Covert channel after analyzing the protocols (IP, TCP, UDP, ICMP) header depends on the field that used in the designing the Covert channel. The access ratio of hidden data in the two protocols TCP/IP was %100. UDP protocol on the other hand depends on a mechanism of unsafe communication. ICMP protocol provided a good transmission, though unreliable, in that the message structure can be unreliable or clear.